2020
DOI: 10.3389/fonc.2019.01557
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Roles of Blood Inflammatory Markers in Hepatocellular Carcinoma Patients Taking Sorafenib. A Systematic Review and Meta-Analysis

Abstract: The purpose of this meta-analysis is to investigate the effectiveness of the prognostic roles of blood inflammatory markers in hepatocellular carcinoma (HCC) patients receiving sorafenib. Methods: We carried out a comprehensive literature search in four databases. Study endpoints, hazard ratios (HRs) and the associated 95% confidence intervals (CI) for clinical outcomes, which were to assess therapeutic efficacy, were extracted. This meta-analysis was conducted by Review Manager 5.3. Results: We summarized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Our study has several limitations. First, we were not able to compute and test the predictive value of immune–inflammatory scores such as PLR [ 60 ], NLR [ 61 ] and SII [ 62 ] since the recording in the ITA.LI.CA database of variables forming these scores started in 2017. Second, we a priori excluded patients’ symptoms as potential prognosticators in order to provide models relying only on standardized parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations. First, we were not able to compute and test the predictive value of immune–inflammatory scores such as PLR [ 60 ], NLR [ 61 ] and SII [ 62 ] since the recording in the ITA.LI.CA database of variables forming these scores started in 2017. Second, we a priori excluded patients’ symptoms as potential prognosticators in order to provide models relying only on standardized parameters.…”
Section: Discussionmentioning
confidence: 99%
“…There are many previous studies that peripheral inflammatory cell-based combination scores like NLR, LMR and PLR have a promising prognostic values in predicting patient survival for HCC in various treatment modalities [55][56][57][58]. In addition, several reports focusing on individual cell types to evaluated the prognostic value in predicting survival for HCC have been published, but these studies investigated patients who performed specific treatment [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a meta-analysis including 5280 HCC patients treated by TACE reported that evaluated NLR and PLR at baseline were significantly correlated with poor OS (HR: 1.81, 95% CI: 1.66-1.97, p < 0.00001; HR: 1.56, 95% CI: 1.13-2.16, p 0.007, respectively) (Li et al, 2020). In addition, another meta-analysis indicated that HCC patients with lower NLR at baseline could have a better response to sorafenib than those with higher pretreatment NLR (HR 1.76, 95% CI: 1.44-2.15, p < 0.00001) (Liu et al, 2019). As shown in the present (Bruix et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the OS and PFS curve showed a cut-off value of median NLR and PLR of 2.42 and 100, which significantly patients' OS and PFS stratified based on NLR and PLR (p < 0.001 for all). A recent meta-analysis indicated that 3 was the minimum cut-off value for NLR to play a prognostic value (Liu et al, 2019). However, different ethnic populations and the heterogeneity of the enrolled studies had a greater impact on the consistency of the results.…”
Section: Discussionmentioning
confidence: 99%